Bioavailability of the major bioactive diterpenoids in a rosemary extract: Metabolic profile in the intestine, liver, plasma, and brain of Zucker rats. Issue 10 (27th April 2013) - Romo Vaquero, María; García Villalba, Rocío; Larrosa, Mar; Yáñez‐Gascón, María J.; Fromentin, Emilie; Flanagan, John; Roller, Marc; Tomás‐Barberán, Francisco A.; Espín, Juan C.; García‐Conesa, María‐Teresa
<x xml:space="preserve">Abstract</x> Scope Carnosic acid (CA) and derived diterpenes abundant in rosemary extracts (REs) exert anti‐obesity effects. The aim of this study was to investigate the bioavailability of these compounds in a rat model of obesity. Methods and results A total of 26 compounds were tentatively identified based on accurate mass information and the isotopic pattern provided by TOF‐MS analyzer. The main metabolites detected in the gut content, liver, and plasma were the glucuronide conjugates of CA, carnosol, and rosmanol. Two other metabolites were also identified: CA 12‐methyl ether and 5, 6, 7, 10‐tetrahydro‐7‐hydroxyrosmariquinone. All the metabolites were detected as early as 25 min following oral administration. Most of the compounds remained in the intestine, liver, and (or) plasma at substantial concentrations for several hours supporting their potential health benefits in these tissues. We also corroborated the presence of small quantities of CA and detected trace quantities of the main CA metabolites in the brain. Notably, we did not find significant differences in the metabolic profile between lean and obese rats. Conclusion We report for the first time a comprehensive profile of metabolites in various organs following the oral consumption of an RE enriched in CA and contribute to establish the potential bioactive molecules.